Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s00438-009-0457-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of conservation and divergence of microsatellites in rice

Abstract: Studies on microsatellite distribution and divergence in related genomes contribute towards understanding of genome evolution in eukaryotes. Despite the availability of whole genome sequences of four rice genomes, occurrence and significance of microsatellites in the rice genome has remained a relatively unexplored area of research. We have aligned genomes of two rice subspecies i.e. indica and japonica to understand the trends of microsatellite conservation and divergence in the rice genome. Nearly 62% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…In other plant species, the most frequent trinucleotide repeat motifs were AAC/TTG in wheat, AAG/TTC in soybean, and CCG/GGC in barley, rice, maize and sorghum [13, 8, 18]. The previous studies on Arabidopsis and soybean [15] also reported abundance of trinucleotide motif AAG, contrasting to the abundance of CCG motif in cereal species [6].…”
Section: Discussionmentioning
confidence: 99%
“…In other plant species, the most frequent trinucleotide repeat motifs were AAC/TTG in wheat, AAG/TTC in soybean, and CCG/GGC in barley, rice, maize and sorghum [13, 8, 18]. The previous studies on Arabidopsis and soybean [15] also reported abundance of trinucleotide motif AAG, contrasting to the abundance of CCG motif in cereal species [6].…”
Section: Discussionmentioning
confidence: 99%
“…Their biological significance to the host genomes has been a topic of debate in recent years. Moreover, little knowledge is available about their mutational dynamics [17, 18], primarily derived from the limited genomewide studies in model organisms [4, 5, 7]. Comprehensive surveys on microsatellite conservation across the species and within duplicated sequences of the same genome are, therefore, required to expand our understanding regarding their genomic significance.…”
Section: Resultsmentioning
confidence: 99%
“…Repeatmasker (http://www.repeatmasker.org/) with WU-blast [12] search engine was used with default sensitivity and rice as “DNA source” for mining of microsatellite repeats, which were subsequently aligned using glocal algorithm [13] in Vista Genome Browser (http://pipeline.lbl.gov/cgi-bin/gateway2) [14] following the method described earlier by Roorkiwal et al [7]. A simple sequence with repeat motif length of 1–6 bp spanning a minimal length of 20 bp was considered as a microsatellite.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some data is available on the distribution of microsatellites in various genomes [6,17], but virtually no information is available till date on genomic distribution of minisatellites and satellites. Our experience of working with microsatellites, i.e., tandem repeats with shorter repeat motifs [7,18] suggests that the structure of tandem repeats may be regulated by their neighbouring components of the genome, as also reported for their mutability [19]. However, coding and non coding regions of a genome are regulated by differrent constraints and thus the fine genomic environment at these sites differs from one another.…”
Section: Discussionmentioning
confidence: 98%